    ### Answers − Solving quadratics of the form x2 + bx + c = 0 by factorising first

#### 1.   Solve x2 + 6x + 8 = 0

 i. From answer 1 in Factorising Quadratics − 1 the factors are: (x + 2)(x + 4) ii. So (x + 2)(x + 4) = 0
 iii. x + 2 = 0 => x = −2 Or x + 4 = 0 => x = −4

#### 2.   Find the values of x where x2 + 9x + 18 = 0

 i. From answer 2 in Factorising Quadratics − 1 the factors are: (x + 3)(x + 6) ii. So (x + 3)(x + 6) = 0
 iii. x + 3 = 0 => x = −3 Or x + 6 = 0 => x = −6

#### 3.   Solve x2 + x − 56 = 0

 i. From answer 3 in Factorising Quadratics − 1 the factors are: (x + 8)(x − 7) ii. So (x + 8)(x − 7) = 0
 iii. x + 8 = 0 => x = −8 Or x − 7 = 0 => x = 7

#### 4.   Find the values of x where x2 + 10x − 24 = 0

 i. From answer 4 in Factorising Quadratics − 1 the factors are: (x + 12)(x − 2) ii. So (x + 12)(x − 2) = 0
 iii. x + 12 = 0 => x = −12 Or x − 2 = 0 => x = 2

#### 5.   Solve x2 − 16x + 60 = 0

 i. From answer 5 in Factorising Quadratics − 1 the factors are: (x − 6)(x − 10) ii. So (x − 6)(x − 10) = 0
 iii. x − 6 = 0 => x = 6 Or x − 10 = 0 => x = 10

#### 6.   Find the values of x where x2 − 15x + 36 = 0

 i. From answer 6 in Factorising Quadratics − 1 the factors are: (x − 3)(x − 12) ii. So (x − 3)(x − 12) = 0
 iii. x − 3 = 0 => x = 3 Or x − 12 = 0 => x = 12

#### 7.   Solve x2 − 8x − 48 = 0

 i. From answer 7 in Factorising Quadratics − 1 the factors are: (x + 4)(x − 12) ii. So (x + 4)(x − 12) = 0
 iii. x + 4 = 0 => x = −4 Or x − 12 = 0 => x = 12 back to:   